2018
DOI: 10.18805/ijar.b-3393
|View full text |Cite
|
Sign up to set email alerts
|

Productive and reproductive performance of cattle and buffaloes reared under farmers’ management in differential dairy progressive states in India

Abstract: The productive and reproductive performances of dairy animals have direct effect to milk production and profitability of dairy enterprise. The present study was carried out to analyse the productive and reproductive performance of cattle and buffaloes reared under farmers’ management in three states of differential dairy progress in India. Haryana, Maharashtra and Odisha states were purposively selected from highly, moderately and least dairy progressive states, respectively. The total sample size was 900 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…ICP of crossbred cattle was 389. 98±21.36, 391.28±19.18 and 398.54±26.15 days in Haryana, Maharashtra and Odisha respectively (Kale et al 2018). Short Inter-calving is important for maximizing herd profitability.…”
mentioning
confidence: 88%
“…ICP of crossbred cattle was 389. 98±21.36, 391.28±19.18 and 398.54±26.15 days in Haryana, Maharashtra and Odisha respectively (Kale et al 2018). Short Inter-calving is important for maximizing herd profitability.…”
mentioning
confidence: 88%
“…One of the most important measures of milch animal performance is optimal lactation length. It is depicted from Kale et al (2018), Kumar (2012), Manjusha et al (2016) and Meena et al (2015).…”
Section: Lactation Length (In Days)mentioning
confidence: 99%
“…Haryana, Maharashtra and Odisha) revealed that the productive and reproductive performances of buffalos in Haryana were better than Maharashtra and Odisha whereas, the productive and reproductive performances of crossbred were found better in Haryana as well as Maharashtra than Odisha. The reproductive performance of buffalo, indigenous and crossbred cow was assessed on the parameters such as age at first calving, services per conception, service period and calving interval while, productive performance was assessed based on the parameters such as average daily milk yield, lactation length, dry period, average lactation milk yield, peak yield (Kale et al, 2018). Similarly, the reproductive and productive performance of dairy animals in Karnal district of Haryana State revealed that average daily milk yield, lactation length, lactation yield and peak yield was higher in crossbred cows as compared to buffalo and indigenous cows (Manjusha et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our indicator approach is in line with the sustainable livelihood framework which was developed by the DFID. The normalization of variables was done as described in the literature [22,23,24] to make it comparable since the variables are in a different scale and unit. Eq.…”
Section: Normalization Of Variablesmentioning
confidence: 99%